Silent invocations : music, sublimation, and social transformation : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Sociology at Massey University, Albany - Bolitho, Wendy Anne (Massey University, 2011)
On the premise that human subjectivity and social bonds are formed through language, Lacanian psychoanalysis is utilised in contemporary cultural and social-political theory as an analytic tool to explore human relationality, identity formation and to ascertain the dynamics of social life in the hope that the worst manifestations of violence and exploitation might be averted. The Lacanian wager suggests that any significant and lasting transformation of human relationality requires the reconfiguration of the unconscious co-ordinates of subjectivity through a particular practice of speech and speaking. In this assertion, however, Lacanian theory appears to present a point of impasse around the inability for the kernel of the human condition (the Lacanian Real) to be negotiated by purely symbolic means. Given that music and musical practices are closely allied to the structure of language and its temporal articulation as speech, but have remained outside psychoanalytic theorisation, this thesis approaches the Lacanian opus from the perspective of artistic musical practices to reassess the mechanisms that forge and reshape human relations and social formations. If cultural practices are the fulcrum upon which the entwinement of the social-political realm and singular instances of subjectivity emerge, then artistic practices and processes – especially musical improvisation and composition – offer a particularly felicitous model to explore and explicate the mechanisms and conditions of contingent possibility through which reconfigurations of social-political life might occur. Applying a wide range of theoretical and practical musical knowledge to the close reading of the English translations of Jacques Lacan's Seminars and writings, this thesis makes the case that 'music' (understood as a performative and creative trans-subjective act of structuring sound) constitutes an alternative form of artistic 'writing practice', and a viewpoint from which a productive analysis and creative expansion of psychoanalytic theory can justifiably be envisaged. To this end, it also identifies the need to reconsider the prevailing emphasis on unconscious fantasy and its traversal in post-Marxist debates, in favour of a rearticulation of the efficacy of artistic practices that Lacan considered to be a privileged form of sublimation capable of social transformation.
Keywords: Jacques Lacan; Lacanian psychoanalysis; Psychoanalysis and music; Music; Social change; Lacan, Jacques